2003
DOI: 10.1590/s1516-89132003000400007
|View full text |Cite
|
Sign up to set email alerts
|

Physiological changes of Candida tropicalis population degrading phenol in fed batch reactor

Abstract: Candida tropicalis can use phenol as the sole carbon and energy source. Experiments regarding phenol degradations from the water phase were carried out. The fermentor was operated as a fed-batch system with oxistat control. Under conditions of nutrient limitation and an excess of oxygen the respiration activity of cells was suppressed and some color metabolites (black-brown) started to be formed. An accumulation of these products inhibited the cell growth under aerobic conditions. Another impact was a decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Pseudomonas is a bacterial genus commonly found in waste water plants and Pseudomonas putida is a species capable of using phenol as a major source, which has been studied (Bayly and Wigmore, 1973;Yang and Humphrey, 1975). In addition, fungi including Trichosporon cutaneum and Candida tropicalis are capable of utilizing phenol as the major carbon and energy source (Neujahr and Varga, 1970;Neujahr et al, 1974;Krug et al, 1985;Krug and Straube, 1986;Stephenson, 1990;Komárková and Páca, 2000;Komárková et al, 2003;Páca et al, 2002;Ahuatzi-Chacon et al, 2004). The aim of the study was to evaluate various packing materials that can be used on an industrial scale in packed bed reactors with immobilized cells in a biofilm.…”
Section: Introductionmentioning
confidence: 99%
“…Pseudomonas is a bacterial genus commonly found in waste water plants and Pseudomonas putida is a species capable of using phenol as a major source, which has been studied (Bayly and Wigmore, 1973;Yang and Humphrey, 1975). In addition, fungi including Trichosporon cutaneum and Candida tropicalis are capable of utilizing phenol as the major carbon and energy source (Neujahr and Varga, 1970;Neujahr et al, 1974;Krug et al, 1985;Krug and Straube, 1986;Stephenson, 1990;Komárková and Páca, 2000;Komárková et al, 2003;Páca et al, 2002;Ahuatzi-Chacon et al, 2004). The aim of the study was to evaluate various packing materials that can be used on an industrial scale in packed bed reactors with immobilized cells in a biofilm.…”
Section: Introductionmentioning
confidence: 99%
“…The marine yeast strains of Candida tropicalis have many potential applications in biodiesel production (Meng et al, 2009), bioremediation (Ukrit et al, 2009;Sonali and Banwari, 2008;Varma and Gaikwad, 2009;Komarkova et al, 2003;Berardi and Goldblatt, 1980;Robinson et al, 2001;Francis et al, 2001;Zhang et al, 2006), polyol sweeteners production (Makinen, 2000;Rao et al, 2004;Cheng et al, 2009;Rao et al, 2006) and ethanol fermentation (Ukrit et al, 2009). For example, recently it has been found that the strain C. tropicalis D04-2.7, which was isolated from the root of biological sample of the mangrove tree Rhizophora stylosa in Zhanjiang, China (Table 1), could accumulate over 50% of oil during batch cultivation from glucose and hydrolysate of cassava starch.…”
Section: Potential Applications Of the Marine Yeast C Tropicalismentioning
confidence: 99%
“…Numerous studies have been carried out with C. tropicalis, such as substrate inhibition of phenol oxidation (Stephenson, 1990), protoplast fusion technique (Chang et al, 1995) and degradation of phenol in the presence of other derivatives (Komarkova et al, 2003). C. tropicalis can also be used to produce xylitol using xylose as the sole carbon source.…”
Section: Introductionmentioning
confidence: 99%
“…It acts as a membrane-actived agent, which increases the permeability of the cytoplasmac membrane and causes a leakage of cytoplasmic material. Little information about the use of yeast cultures grown on phenolic compounds is found in the literature (Páca et al, 2002;Ruiz-Ordaz et al, 1998;Komarkova et al, 2003), especially the catechol that is considered more toxic than phenol Kumar et al,(2005). There are some phelolytic microorganisms that show different behaviour in terms of their ability to degrade these compounds.…”
Section: Introductionmentioning
confidence: 99%